Evaluation of kidney size in children: a pilot study of renal length as a surrogate of organ growth - Boo Won Kim; Min Kyoung Song; Sochung Chung; Kyo Sun Kim (Korean Pediatric Society, 2012)
PurposeSomatic growth is an important indicator of health in children. Adequate organ growth is essential in growth and directly related to body growth. We consider renal length as a surrogate of organ growth in growing children. Measurement of weight, height, and many anthropometric indices, such as body surface area (BSA), body mass index (BMI), and Rohrer and Kaup indices, are used to evaluate growth status. The aim of this study was to evaluate the association between renal length and somatic parameters and analyze the affecting factors for renal size during growth.MethodsThe data for renal length in 66 children (age, 12.9±15.6 months; male/female, 34/32) were obtained. Each kidney was measured with ultrasonography and dimercaptosuccinic acid scan. The data on age, sex, height, and weight were obtained from the medical records. BSA, BMI, and Rohrer and Kaup indices were calculated from measured height and weight. BSA was calculated by 2 methods, and is expressed as BSA I and BSA II.ResultsThere were significant correlations between renal size and age, weight, height, BSA I, BSA II, and Rohrer index. In the regression analysis, the most significant contributing factor to renal growth was height (R2=0.636, P<0.001).ConclusionHeight seems to be the most important factor associated with organ growth in growing children. Further studies to evaluate adequate organ growth should be carried out.